Case Report: Syndrome of inappropriate antidiuretic hormone secretion induced by pramipexole: a case report and literature review - Ke-Qian Chen; Xiang Liu; Hai-Bo Lei (Frontiers in Pharmacology)
Pramipexole, a novel dopamine receptor agonist, is widely used in the treatment of Parkinson’s disease and related syndromes. While studies have demonstrated that pramipexole can cause various adverse reactions, primarily involving the central nervous system or gastrointestinal symptoms, there remains limited reporting on pramipexole-induced syndrome of inappropriate antidiuretic hormone secretion (SIADH). This article analyzes and discusses a case of pramipexole-induced SIADH that occurred in our hospital. At the same time, we also summarize and discuss all current cases of pramipexole-induced SIADH. We anticipate these findings will serve as a valuable clinical reference to guide appropriate medication use.